2005
DOI: 10.4314/eamj.v82i3.9273
|View full text |Cite
|
Sign up to set email alerts
|

Calcium deficiency and causation of rickets in Ethiopian children

Abstract: Objective: To assess the role of calcium in the development of clinical rickets among Ethiopian children coming to Jimma Specialised Hospital outpatient, department. Design: Case control study. Settings: Jimma Specialised Teaching Hospital and surrounding urban and rural community in the catchment area. Subjects: One hundred and thirty five under five year old children (30 cases of rickets and 104 non-rachitic cases) who came for paediatric service in Jimma hospital. Results: The mean (±SD) level of calcium in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…A work done Tezera, Whiting, & Gebremedhin (2017) showed that calcium intake by children was below the recommended level. A study conducted on under-five children in Jima, Oromia region, also in Ethiopia, showed that the majority of the study participants were taking calcium below the recommended level (Belachew et al, 2005). Similarly, a recent study conducted by showed that almost 100% of children aged 6-23 months old have inadequate intake of calcium.…”
Section: Calcium Inadequate Intake and Factors That Increased The Risksmentioning
confidence: 93%
“…A work done Tezera, Whiting, & Gebremedhin (2017) showed that calcium intake by children was below the recommended level. A study conducted on under-five children in Jima, Oromia region, also in Ethiopia, showed that the majority of the study participants were taking calcium below the recommended level (Belachew et al, 2005). Similarly, a recent study conducted by showed that almost 100% of children aged 6-23 months old have inadequate intake of calcium.…”
Section: Calcium Inadequate Intake and Factors That Increased The Risksmentioning
confidence: 93%